1983
DOI: 10.1136/bmj.287.6400.1167
|View full text |Cite
|
Sign up to set email alerts
|

Ulceration of the hand secondary to a radial arteriovenous fistula: a model for varicose ulceration.

Abstract: Blood glucose concentrations in a woman with severe retinopathy, nephropathy, and neuropathy were found to be within the normal range. A high random blood glucose concentration was recorded only once, six months before her initial presentation. At necropsy the anterior lobe of the pituitary gland showed old, extensive infarction.Occult pituitary hypofunction may explain severe diabetic microangiopathy in patients with normal glucose tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“…91 Pericapillary cuffs, dermal edema, and intimal proliferation were observed in biopsy specimens taken from the index finger or first web space of patients with upper extremity access grafts and signs of venous hypertension. 89,90 Peroxidase-antiperoxidase staining confirmed the presence of fibrin. 90 Monoclonal antibodies and immunofluorescence studies confirmed the presence of fibrin in the cuffs as well as plasminogen activator inhibitor-1; the latter is suggestive of impaired breakdown of fibrin.…”
Section: Clinical Features Of V-htnmentioning
confidence: 82%
See 4 more Smart Citations
“…91 Pericapillary cuffs, dermal edema, and intimal proliferation were observed in biopsy specimens taken from the index finger or first web space of patients with upper extremity access grafts and signs of venous hypertension. 89,90 Peroxidase-antiperoxidase staining confirmed the presence of fibrin. 90 Monoclonal antibodies and immunofluorescence studies confirmed the presence of fibrin in the cuffs as well as plasminogen activator inhibitor-1; the latter is suggestive of impaired breakdown of fibrin.…”
Section: Clinical Features Of V-htnmentioning
confidence: 82%
“…89,90 Peroxidase-antiperoxidase staining confirmed the presence of fibrin. 90 Monoclonal antibodies and immunofluorescence studies confirmed the presence of fibrin in the cuffs as well as plasminogen activator inhibitor-1; the latter is suggestive of impaired breakdown of fibrin. Less extensive fibrin cuffs were also observed in two side-to-side autogenous AV accesses, but none in three end-to-end autogenous AV accesses or controls.…”
Section: Clinical Features Of V-htnmentioning
confidence: 82%
See 3 more Smart Citations